2022
DOI: 10.1111/jcpt.13763
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different sedatives in children before general anaesthesia for selective surgery: A network meta‐analysis

Abstract: What is known and Objective It is estimated that 60% of children undergoing anaesthesia develop severe preoperative anxiety. The anxiety is associated with adverse reactions. Sedatives such as dexmedetomidine, midazolam, clonidine, ketamine, and melatonin can be used as premedication against preoperative anxiety. However, no consensus has been reached on the choice of pre‐anaesthetic sedatives in children before selective surgery. Therefore, the current network meta‐analysis (NMA) was carried out to evaluate d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…Giving sedative medications like benzodiazepines at home carries the risk of airway obstruction, over-sedation, and respiratory depression when co-administered with perioperative opioids, especially in children with pre-existing diseases and syndromes. Clonidine is an effective pre-medication that may exhibit fewer respiratory concerns [ 1 , 2 , 3 ]. This is the first reported case series of pediatric patients receiving clonidine as a pre-admission premedication for the treatment of severe perioperative anxiety and/or behavioral concerns.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Giving sedative medications like benzodiazepines at home carries the risk of airway obstruction, over-sedation, and respiratory depression when co-administered with perioperative opioids, especially in children with pre-existing diseases and syndromes. Clonidine is an effective pre-medication that may exhibit fewer respiratory concerns [ 1 , 2 , 3 ]. This is the first reported case series of pediatric patients receiving clonidine as a pre-admission premedication for the treatment of severe perioperative anxiety and/or behavioral concerns.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative anxiety is common in children, most commonly between ages 1–7 years, undergoing diagnostic and therapeutic procedures under anesthesia, and can lead to significant adverse effects, such as emergence delirium, increased analgesic doses in the recovery room, behavioral problems post-operatively, and post-traumatic stress disorder [ 1 ]. Several medication classes have been studied to treat anxiety and enhance cooperation in the pre-operative period, including benzodiazepines, ketamine, and alpha-2 adrenergic agonists.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fentanyl is an opioid analgesic like pethidine ( 20 ). Midazolam is a short-acting benzodiazepine, which has the effects of anti-anxiety, sedation, hypnosis, and muscle relaxation but with side effects such as respiratory depression ( 21 , 22 ). We find that promethazine-pethidine treatment showed a tendency for milder liver injury than midazolam-fentanyl in patients 7-day after severe burns.…”
Section: Discussionmentioning
confidence: 99%
“…Drugs with α 2 -agonistic effects have played an essential role in veterinary anaesthesia for a long time; in humans, clonidine and dexmedetomidine are increasingly used for premedication, sedation or as co-analgesic compounds. Dexmedetomidine is considered to be a suitable [12 ▪ ] or even superior agent [13] for premedication compared with midazolam; this judgement was mainly based on the observation of more peaceful recovery and improved postoperative analgesia. However, recently two articles comparing midazolam with clonidine [7 ▪▪ ] and midazolam with clonidine and dexmedetomidine [8 ▪▪ ] showed that α 2 -agonists cause marked sedation, but virtually no anxiolysis.…”
Section: Premedicationmentioning
confidence: 99%